ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI TEBU TANAM DAN KEPRASAN DI KABUPATEN BANTUL - Wasilatur Rohmah; Any Suryantini; Slamet Hartono (Agro Ekonomi, 2014)
This study aimeds to determine (1) factors affecting sugarcane production (2) factors affecting the sugarcane income (3) the risk ofsugarcane production and income (4) contribution of sugarcane farm-income to farmer households’ income (5) income distribution among farmer households (6) the level of farmer households’ welfare in Bantul District. The basic method of this research was descriptive analytical, sample was chosen  purposively. Number of respondent was 30 sugarcane farmers. Analytical tools were the Cobb-Douglas production function and Unit Output Price (UOP) profit function. The result showed that (1) factors that positively influencing to the sugarcane production were land acreage, sugarcane seedlings, ZA fertilizer, pesticides, cultivating labor, harvesting labor and cropping method (2) factor that positively influencing to the sugarcane income was land acreage. Income factor that had negatively influence to the sugarcane income were sugarcane seedling’s price and cultivating labor’s wage (3) production risk of second ratoon sugarcane  was the highest among other sugarcane planting systems. Income risk of second ratoon sugarcane  was the highest among other sugarcane planting system (4) contribution of sugarcane income to the farm household income was the majority (5) sugarcane income could improve farm household’s income distribution (6) sugarcane farm-households was classified as a prosperous household.